The PHEMU15 catalogue and astrometric results of the Jupiter's Galilean satellite mutual occultation and eclipse observations made in 2014–2015. Issue 4 (21st November 2017) - Saquet, E; Emelyanov, N; Robert, V; Arlot, J-E; Anbazhagan, P; Baillié, K; Bardecker, J; Berezhnoy, A A; Bretton, M; Campos, F; Capannoli, L; Carry, B; et al.
Abstract: During the 2014–2015 mutual events season, the Institut de Mécanique Céleste et de Calcul des Éphémérides (IMCCE), Paris, France, and the Sternberg Astronomical Institute (SAI), Moscow, Russia, led an international observation campaign to record ground-based photometric observations of Galilean moon mutual occultations and eclipses. We focused on processing the complete photometric observations data base to compute new accurate astrometric positions. We used our method to derive astrometric positions from the light curves of the events. We developed an accurate photometric model of mutual occultations and eclipses, while correcting for the satellite albedos, Hapke's light scattering law, the phase effect, and the limb darkening. We processed 609 light curves, and we compared the observed positions of the satellites with the theoretical positions from IMCCE NOE-5-2010-GAL satellite ephemerides and INPOP13c planetary ephemeris. The standard deviation after fitting the light curve in equatorial positions is ±24 mas, or 75 km at Jupiter. The rms (O−C) in equatorial positions is ±50 mas, or 150 km at Jupiter.